1997
DOI: 10.1021/jo970554t
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Photochemical Reactions of Bichromophoric 3-(Alkenyloxy)phenols and 1-(Alkenyloxy)-3-(alkyloxy)benzene Derivatives. Acid-Catalyzed Transformations of the Primary Cycloadducts

Abstract: Irradiation of 3-(alkenyloxy)phenols and 1-(alkenyloxy)-3-(alkyloxy)benzene derivatives, at λ = 254 nm in acidic media, yields benzocyclobutenes, 3-alkylphenols, 3-alkylanisols, and 4-alkyl-1,2-dialkyloxybenzenes depending on the substitution pattern of the aromatic ring and the olefinic side chain. The final products are derived from an intramolecular [2 + 2] photocycloaddition and acidic rearrangements from a common intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Melting points were measured in open capillary tubes on a Stuart SMP3 apparatus and are uncorrected. NMR spectra were recorded on Bruker spectrometers operating at 500 or 600 MHz for 1 H, 126 or 151 MHz for 13 C{ 1 H}, and 471 MHz for 19 F. For 1 H NMR spectra, chemical shifts are reported in parts per million (ppm) with reference to tetramethysilane (δ = 0.00 ppm) or a residual protonated solvent (δ = 7.26 ppm for CHCl 3 , δ = 1.94 ppm for CD 3 CN) as an internal standard. For 13 C{ 1 H} NMR spectra, chemical shifts are reported in parts per million (ppm) with reference to the deuterated solvent (δ = 77.16 ppm for CDCl 3, δ = 1.03 ppm for CD 3 CN) as an internal standard.…”
Section: ■ Conclusionsupporting
confidence: 65%
See 3 more Smart Citations
“…Melting points were measured in open capillary tubes on a Stuart SMP3 apparatus and are uncorrected. NMR spectra were recorded on Bruker spectrometers operating at 500 or 600 MHz for 1 H, 126 or 151 MHz for 13 C{ 1 H}, and 471 MHz for 19 F. For 1 H NMR spectra, chemical shifts are reported in parts per million (ppm) with reference to tetramethysilane (δ = 0.00 ppm) or a residual protonated solvent (δ = 7.26 ppm for CHCl 3 , δ = 1.94 ppm for CD 3 CN) as an internal standard. For 13 C{ 1 H} NMR spectra, chemical shifts are reported in parts per million (ppm) with reference to the deuterated solvent (δ = 77.16 ppm for CDCl 3, δ = 1.03 ppm for CD 3 CN) as an internal standard.…”
Section: ■ Conclusionsupporting
confidence: 65%
“…13 C{ 1 H} NMR (126 MHz, CDCl 3 ): δ 153.4 (ddd, J = 286.1, 272.2, 47.4 Hz; CF 2 ), 152.4 (Cq), 150.0 (Cq), 128.5 (ddd,J = 234.6,53.4,15.3 Hz;CF),126.5 (CH),119.4 (CN), 114.4 (CH), 112.5 (CH), 104.0 (Cq), 68.6 (CH 2 ), 56.3 (CH 3 ), 28.1 (CH 2 ), 25.4 (dd, J = 22.0, 1.7 Hz; CH 2 ), 22.2 (CH 2 ). 19 F NMR (471 MHz, CDCl 3 ): δ −105.3 (dd, J = 88.7, 32.3 Hz, 1F; C-F), −124.5 (dd, J = 114.1, 88.7 Hz, 1F; C-F 2 ), −174.5 (dd, J = 114.1, 32.3 Hz, 1F; C-F 2 ). IR: ν (cm −1 ) 2945,2870,2223,1797,1597,1581,990,877,817,797,737,693 Procedure for the Preparation of 3-Methoxy-4-( (3,4,4-trifluorobut-3-en-1-yl)oxy)benzonitrile (10e).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hoffmann and Pete and co-workers later showed that phenol derivatives also give ortho adducts, which rearrange in situ under acidic catalysis into benzocyclobutane derivatives (Scheme ). Interestingly, the benzocyclobutanes were later exploited in thermal generation of orthoquinodimethane and subsequent trapping with a dienophile .…”
Section: Ortho Cycloadditionmentioning
confidence: 99%